Influence of a surface modification of natural clay components soil on the desorption of cesium - Kobets, S. A.; Fedorova V. М.; Pshinko, G. N.; Goncharuk, V. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The cesium desorption from model-based samples of montmorillonite from the Cherkassy deposit is studied. On their surface, humic acids or hydroxides of Fe(III) are deposited by ammonium salts, which are placed by its leaching capacity in a row: NH4Cl < NH4H2Cit < (NH4)2Ox < (NH4)2HCit. The most effective and environmentally viable in the neutral pH range as leaching reagents for cesium ions are 0.1 M/l solutions of disubstituted disodium citrate ammonium salts.